2003
DOI: 10.1051/agro:2003010
|View full text |Cite
|
Sign up to set email alerts
|

Kinetin alleviates the influence of waterlogging and salinity on growth and affects the production of plant growth regulators in Vigna sinensis and Zea mays

Abstract: Growth criteria (shoot height, root length and dry weight) of 14-d-old Vigna sinensis and Zea mays were mostly suppressed by waterlogging or salinization using artificial seawater mixture during the subsequent 3 weeks; the water level in pots was, respectively, kept at 120% or 60% of water field capacity. The suppression in growth induced by salinization was greater than that obtained by waterlogging. The pattern of changes in growth appeared similar to chlorophyll a and b as well as activity of d-aminolevulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…Very close results have been reported by El-Sayed (2011), Gauch and Wadleigh (1951) and Younis et al (2003). Salinity affects almost every aspect of the physiology and biochemistry of plants and significantly reduces yield.…”
Section: Results and Discussion Early Growth Response Of Broad Bean supporting
confidence: 82%
“…Very close results have been reported by El-Sayed (2011), Gauch and Wadleigh (1951) and Younis et al (2003). Salinity affects almost every aspect of the physiology and biochemistry of plants and significantly reduces yield.…”
Section: Results and Discussion Early Growth Response Of Broad Bean supporting
confidence: 82%
“…Water logging results in wilting, chlorosis, senescence and abscission of leaves which may be due to reduced uptake and mobilization of nutrients. Reduction in chlorophyll content was also reported in pigeonpea [43,44], wheat [45], maize [46] and Vigna sinensis [47]. The highly significant negative correlation between reduction in chlorophyll content and plant survival indicated that high reduction in chlorophyll after water logging and saline treatments disrupted plant metabolism which led to plant mortality.…”
Section: Discussionmentioning
confidence: 64%
“…Jackson et al (1982) reported waterlogging induced membrane damage in pea plants resulting in more than 40 times increase in solute leakage. Waterlogging induced decline in Chl contents have been reported in wheat (Collaku and Harrison 2002), Vigna sinensis (Younis et al 2003) and soybean (Sorte et al 1996). Pigeon pea plants visually wilted within 4 d of imposing of flooding stress due to the higher resistance to mass flow of water through the roots (Jackson and Drew 1984).…”
Section: Discussionmentioning
confidence: 98%